Pengaruh Experiential Marketing dan Kepuasan Pelanggan Terhadap Minat Beli Ulang (Studi Kasus pada Wirskopi 2.0 Makassar) - Ina Lapparan; Hety Budiyanti; Muhammad Ilham Wardhana Haeruddin (Journal of Management and Creative Business, 2025)
LAPPARAN, INA, 2024. The Influence of Experiential Marketing and Customer Satisfaction on Repurchase Intention (Case Study at Wirskopi 2.0 Makassar). Undergraduate Thesis. Management Study Program, Faculty of Economics and Business, State University of Makassar. Supervised by Hety Budiyanti and Muhammad Ilham Wardhana Haeruddin. This study aims to determine the impact of experiential marketing and customer satisfaction on repurchase intention at Wirskopi 2.0 Makassar. The population includes all visitors who have visited Wirskopi 2.0 Makassar at least three times within a month. The sampling technique used is non-probability sampling with a purposive sampling method. The research employs a quantitative approach, with multiple linear regression analysis and data processing using SPSS version 25. The hypothesis testing results indicate that experiential marketing and customer satisfaction have a partial and simultaneous effect on repurchase intention at Wirskopi 2.0 Makassar. The coefficient of determination shows that 26% of the variance in repurchase intention is explained by experiential marketing and customer satisfaction, while the remaining 76% is influenced by other variables outside this study.